Durability of materials under repeated dynamic loading - Murzakhmetova, U. A.; Seitkazenov, K. K.; Alshynova, A. M. (Харківський національний автомобільно-дорожній університет, 2023)
The regularities of micro-shock fatigue destruction of annealed metal materials under severe loading conditions are revealed. Based on the law of summation of damages and taking into account the features of crack formation in dynamically deformed volumes of wear materials, a model is obtained for erosion. The generalization of the obtained private model at the micro - macroscale level of wear made it possible to obtain a universal power dependence suitable for assessing the durability of materials. The law of summation of damages for stepped loading is presented .
Довговічність матеріалів при повторному динамічному навантаженні
Keywords: crack; wear; erosion; fatigue life; 620.178